Feline gastrointestinal eosinophilic sclerosing fibroplasia - Nicolás Enríquez; Castro, Diana A. Ríos; López, Paola A. Bedoya; Velásquez, Carlos A. Chaves; Calvache, Tatiana G. Paz (Brazilian Journal of Veterinary Pathology, 2022)
A female Persian cat arrives for clinical assessment with a 3-month history of weight loss and sporadic vomiting. The clinical and paraclinical findings were hypodynamia cachexia, leukocytosis and presence of a mass in duodenum. Histopathological evaluation revealed a non-neoplastic tumor proliferation, which was organized into dense, sclerotic-like connective tissue trabeculae that anastomosed, with cells of spindle-shaped morphology, elongated and rounded nuclei with prominent nucleoli and fine granular chromatin. These cells were intermingled with abundant eosinophils and in smaller proportion lymphocytes, macrophages, plasma cells, with transmural distribution. Masson’s trichrome differential staining trabeculae of collagen fibers. Based on the clinical and microscopic findings, the diagnosis of feline eosinophilic sclerosing fibroplasia is established, being this pathology’s first documented report in Colombia.